ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI INTELLECTUAL CAPITAL DISCLOSURE PADA PERUSAHAAN JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2017-2019 - Eunike Rosni Bohalima; Alsemeta Natafati Zai; Wilsa Road Betterment Sitepu (AKUNTANSI DEWANTARA, 2021)
The main objective of this research is to explore further the various factors that can influence the disclosure of intellectual capital. This test uses independent variables auditor reputation, leverage, independent commissioner, and profitability. Service companies listedÂ on the IDX in the 2017-2019 period were used as the population in this test with a total population of 432 companies. The samples were determined by the purposive sampling method which resulted in a final total of 120 samples from 40 companies. Tests were carried out through multiple linear regression analysis techniques and using SPSS version 25 for windows as a data processing medium.Â Judging from the partial test, the results of this test show that only the leverage and profitability factors affect intellectual capital disclosure, while the independent commissioner and auditor's reputation variables do not affect intellectual capital disclosure. Judging from the simultaneous test, this test shows that the independent variables of auditor reputation, leverage, independent commissioner, and profitability have a simultaneous effect on the dependent variable of intellectual capital disclosure.